Electroencefalografía en Caninos - Díaz Lozano, Nicole Tatiana; Rodríguez Salazar, Ana María; Vásquez Nivia, Cristian Ernesto (Universidad Antonio Nariño, 2023)
The frequency of seizures in canines fluctuates from 0.5% to 5.7% of consultations at the small animal clinic, where 80% are caused mainly due to idiopathic epilepsy (Goiz, 2008) which has been of interest, and object of study as recorded in the literature (Thomas, 2010) (Ekenstedt, 2013), due to the increase in queries for this reason.